Gravity Model Analysis of Indonesia's Trade Role within OIC Economies - Ula, Tajul (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
Indonesia, possessing the largest economic volume among Muslim-majority countries, plays a pivotal role in the global economy, particularly through its export activities. This study examines the factors influencing Indonesia's export performance and its economic interactions with the five largest economies within the Organization of Islamic Cooperation (OIC) member countries: Saudi Arabia, Turkiye, Iran, Nigeria, and the United Arab Emirates. Utilizing a random effect panel data model, the analysis spans from 1989 to 2021. The findings reveal that variables such as GDP, Distance, Economic Similarity Index, and Exchange Rate of these OIC countries positively impact Indonesia's exports. Additionally, Indonesia's exports significantly contribute to the GDP growth of these OIC nations. The study underscores the importance of Indonesia's trade in enhancing the economic capacities of OIC partner countries, thereby boosting national economic output and foreign exchange reserves. The results advocate for the revitalization of trade agreements and the maintenance of conducive relations among OIC countries to fortify their collective economic strength.========================================================================================================ABSTRAK – Analisis Model Gravitasi Peran Perdagangan Indonesia di Negara-negara OKI. Sebagai salah satu negara dengan volume ekonomi terbesar diantara negara-negara Organisasi Kerjasama Islam (OKI), Indonesia memainkan peran penting dalam perekonomian global, terutama melalui kegiatan ekspornya. Kajian ini menganalisis faktor-faktor yang mempengaruhi kinerja ekspor dan interaksi ekonomi Indonesia dengan lima negara OKI dengan ekonomi terbesar, yaitu Arab Saudi, Turki, Iran, Nigeria, dan Uni Emirat Arab, periode dari tahun 1989 hingga 2021. Menggunakan model data panel random effect, temuan penelitian menunjukkan bahwa variabel seperti PDB, Jarak, Indeks Persamaan Ekonomi, dan Kurs dari negara-negara OKI tersebut berdampak positif pada ekspor Indonesia. Selain itu, ekspor Indonesia secara signifikan berkontribusi terhadap pertumbuhan PDB negara-negara OKI tersebut. Penelitian ini menekankan pentingnya perdagangan Indonesia dalam meningkatkan kapasitas ekonomi negara-negara mitra OKI, sehingga meningkatkan output ekonomi nasional dan cadangan devisa. Hasil ini mendorong revitalisasi perjanjian perdagangan dan pemeliharaan hubungan yang kondusif di antara negara-negara OKI untuk memperkuat kekuatan ekonomi kolektif mereka.